2020
DOI: 10.3390/foods9121909
|View full text |Cite
|
Sign up to set email alerts
|

Grain Quality, Provitamin A Carotenoid Profiles, and Sensory Quality of Provitamin A-Biofortified Maize Stiff Porridges

Abstract: Provitamin A-biofortified maize could contribute to the alleviation of vitamin A deficiency (VAD), which is prevalent in sub-Saharan Africa due to a high consumption of starchy, maize-based diets. Four varieties of provitamin A biofortified maize were studied for grain colour, grain texture, thousand kernel weight, and hectolitre mass. Provitamin A biofortified maize stiff porridges were prepared and their retained provitamin A was determined using lutein, zeaxanthin, β-cryptoxanthin, and β-carotene (all-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In general, all the flours had higher L* values and lower a* values, which is desirable in developing instant porridges. The L*, a* and b* values of the yellow PVABM of the current study were slightly higher than the values reported by Pillay et al [9] and Beswa et al [29]. However, the L* and b* values of the white maize in this study were higher, whereas a* values were lower than those reported by Beswa et al [29] [29] were 46.3, 6.3 and 24.6, respectively.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…In general, all the flours had higher L* values and lower a* values, which is desirable in developing instant porridges. The L*, a* and b* values of the yellow PVABM of the current study were slightly higher than the values reported by Pillay et al [9] and Beswa et al [29]. However, the L* and b* values of the white maize in this study were higher, whereas a* values were lower than those reported by Beswa et al [29] [29] were 46.3, 6.3 and 24.6, respectively.…”
Section: Resultscontrasting
confidence: 78%
“…The L*, a* and b* values of the yellow PVABM of the current study were slightly higher than the values reported by Pillay et al [9] and Beswa et al [29]. However, the L* and b* values of the white maize in this study were higher, whereas a* values were lower than those reported by Beswa et al [29] [29] were 46.3, 6.3 and 24.6, respectively. There was nothing found in the literature on the L*, a* and b* values for the whole grains, oven-dried grains and flours of the BGN varieties and that of the oven-dried grains and flours of both of the maize varieties.…”
Section: Resultscontrasting
confidence: 78%
“…The favoring of orange maize porridge by the children could be attributed to improvements in orange maize porridge attributes as compared to in white maize porridge. A similar study [ 22 ] reported that biofortified maize porridge is finer in texture and has an intense cooked maize flavour and aroma than white maize porridge. Furthermore, another related study [ 23 ] also reported that provitamin-A biofortified maize varieties are not as hard as white maize varieties and are as such more suitable to making stiff porridge than the white maize since porridge requires grain with fairly low hardness.…”
Section: Resultsmentioning
confidence: 96%
“…Further, CS/CAEE-coated sample retained better glossiness ( p < 0.05) at a higher angle during the storage period; however, it slightly decreased at the end of storage. The retention of glossiness in CAEE-coated fruits could be ascribed to the presence of carotenoids . Therefore, based on the obtained results, it could be postulated that CS-based coating maintained the glossiness of fruits while storing for longer periods by modifying the outer surface of the fruits, which could provide a better reflection of light.…”
Section: Results and Discussionmentioning
confidence: 99%